Security concerns of Europe and Asia - Lim, Paul (Universiti Kebangsaan Malaysia, 2002)
What can be drawn out of this paper is that European security will be very much closer to Europe’s shores like Central and Eastern Europe, the Mediterranean Basin and the Middle East. At the wider level, it will be EU-US relations. However, with the development of the Common European Security and Defence Policy, it is said that the Rapid Reaction Force could operate far from Europe’s shores. Will this include Asia? This is left to be seen as this Force remains nascent. For Asian states, do they have concern for European security? It appears that it remains to be much more declaratory within the ASEAN, ASEM or ARF context although we see contingents of Asian troops in Bosnia for example. There seems to be the attitude that the Europeans themselves can deal with their own security.